Exploring the electronic and mechanical properties of lithium-decorated silicon carbide nanowires for energy storage. (June 2023) - Gonzalez, Mario; Salazar, Fernando; Trejo, Alejandro; Miranda, Álvaro; Nava, Rocío; Pérez, Luis Antonio; Cruz-Irisson, Miguel
Abstract: The high chemical stability of silicon carbide (SiC) is attractive to inhibit unwanted side chemical reaction and prolongate the cyclability performance of lithium ion batteries anodes. However, SiC has high surface lithiation energy barrier due to its intrinsic nature and the low electrical conductivity limited the application in this area. The surface modification of SiC is an alternative to boost the lithiation–delithiation kinetics. Hydrogen incorporation on SiC surface is extensively used in semiconductor industry to passivate electrically active centers. In this work, we present a theoretical study of the effect of surface lithium (Li) atoms on the electronic and mechanical properties of hydrogen passivated SiC nanowires (H-SiCNWs) with zinc-blende structure. The results show that the adsorption of Li on the carbon (C) atoms at the surface of the nanowire introduces new electronic states within the former band gap of the H-SiCNWs, whose main contribution comes from the C and silicon (Si) atoms in the valence and conduction bands, respectively. Moreover, the number of new bands within the former band gap increases as a function of the concentration of Li atoms and the systems remain as intrinsic semiconductors up to the maximum Li concentrations. The formation energy reveals that the stability of the nanowires increases when the concentration of Li atoms augments. Moreover, the values of the open circuit voltage are found between 1.6 and 1.9 V for all studied concentrations of Li atoms and morphologies. The charge population analysis indicates that the Li atoms give up charge to the C ones resulting in ionic bonds. On the other hand, the Young modulus of the H-SiCNWs increases when their diameter augments and their values are lower than that of the bulk SiC. Besides, the Young modulus slightly diminishes when the concentration of Li grows, then the mechanical resistance could offer a large useful life of the electrode. Finally, the maximum theoretical storage capacity values indicate that the SiC nanowires (SiCNWs) are good potential anodic materials for rechargeable Li-ion batteries. Graphical abstract: Unlabelled Image Highlights: The SiC nanowires with surface Li atoms remain as intrinsic semiconductors. The Li atoms at the surface of the SiC nanowires reduces the energy band gap. The formation energy of the SiCNWs improves when the concentration of Li atoms augments. The ionic bond CLi facilities the charge/discharge process of Li atoms. The SICNWs maintain a strong mechanical resistance upon adsorption of Li atoms.